Efficacy of overnight leave-on sandwich therapy with 5% cysteamine and ectoine cream compared to hydroquinone 4% cream for treatment of melasma - Kusumawardani, Arie (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Introduction: Melasma is a common hypermelanosis presenting as dark patches on sun-exposed skin. Its treatment remains challenging due to slow response, especially in chronic cases. This study compares the efficacy of 5% cysteamine with ectoine cream versus 4% hydroquinone with ectoine cream in treating melasma. Methods: A double-blind randomized controlled trial was conducted from January to March 2024 across three centers in Indonesia: Dr. Moewardi Hospital (Surakarta), Gatot Soebroto Army Hospital (Jakarta), and Dr. Saiful Anwar Hospital (Malang). Participants were randomly assigned to Group A (5% cysteamine + ectoine) or Group B (4% hydroquinone + ectoine). Efficacy was evaluated using the modified Melasma Area and Severity Index (mMASI) and the JANUS-I skin analyzer. Quality of life was assessed using Melasma Quality of Life Scale (MELASQoL) and Dermatology Life Quality Index (DLQI) questionnaires. Results: Both groups demonstrated reduced mMASI and JANUS-I scores, with slightly greater improvement in Group A, although the difference was not statistically significant (p > 0.05). Quality of living also improved in both groups, with no significant difference between them (p > 0.05). Conclusions: Both treatment regimens effectively improved melasma pigmentation and QoL. Either 5% cysteamine with ectoine or 4% hydroquinone with ectoine can be considered viable treatment options for melasma.
Keywords: cisteamin; cysteamine; hidrokinon; hydroquinone; kakovost življenja; melasma; melazma; quality of life; terapevtsko; therapeutic